Maintenance of sinus rhythm after electrical cardioversion to identify patients with persistent atrial fibrillation who respond favorably to pulmonary vein isolation: the pre-pacific study - Limite, Luca Rosario; Laborie, Guillaume; Ramirez, F. Daniel; Albenque, Jean-Paul; Combes, Stephane; Lagrange, Philippe; Khoueiry, Ziad; Bortone, Agustín (Frontiers in Cardiovascular Medicine, 2024)
Background Pulmonary vein isolation (PVI) is successful in approximately 50% of patients with persistent atrial fibrillation (PsAF) at one year. Identifying pre-procedurally the patients who respond favorably to a PVI alone strategy could improve their management. The present study aims to assess the predictive value of clinical response to pre-ablation electrical cardioversion (ECV) to identify the responders to PVI. Methods Consecutive patients undergoing catheter ablation for PsAF were retrospectively classified, as “ECV successful” vs. “ECV failure”, according to the rhythm of presentation after an ECV performed ≥4 weeks. Clinical and procedural data were analyzed in both groups according to the ablation strategy applied (PVI vs. PVI + substrate modification). Results In total, 58 patients (39.4%) had successful ECVs and 89 (60.6%) had failed ECV. Preprocedural characteristics were similar in both groups. Compared to the ECV failure group, patients with successful ECV presented less frequently (34% vs. 60%; P = 0.004) and less extended (21.3 ± 22.2% vs. 38.9 ± 27.4% of LA surface, P = 0.008) low-voltage areas. Over 55 ± 19 weeks of follow-up, AF-free survival was similar in both groups (72.7% vs. 67.8%, p = 0.39). PVI alone resulted in 83% AF-free survival among patients in the ECV successful group at 13 months. Conclusion In approximately 40% of patients with PsAF, sinus rhythm can be restored by ECV and maintained for at least 1 month prior to catheter ablation. This clinical response is associated with less abnormal substrate as identified by left atrial voltage mapping and a procedural success rate of >80% with PVI alone.